ANALISIS KEAKTIFAN BELAJAR SISWA MENGGUNAKAN MODEL PROJECT BASED LEARNING DENGAN PENDEKATAN STEM PADA PEMBELAJARAN FISIKA MATERI ELASTISITAS DI KELAS XI MIPA 5 SMA NEGERI 2 JEMBER - Nanda Rizky Fitrian Kanza; Albertus Djoko Lesmono; Heny Mulyo Widodo (JURNAL PEMBELAJARAN FISIKA, 2020)
This research describes the subject of elasticity using the Project Based Learning (PjBL) model with the STEM approach to improve students activeness. This research implemented for XI MIPA 5 class at 2 Jember Senior High School in the 2019/2020 academic year during August until September 2019. Data were collected through observation and interviews. This data were analyzed descriptively. The results showed that the Project Based Learning model with the STEM (Sains, Technology, Engineering, and Mathematics) approach could increase of students activeness for XI MIPA 5 class at 2 Jember Senior High School of elasticity material.